Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10508-016-0880-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Men’s Concern About Demonstrating Masculine Characteristics and Their Sexual Risk Behaviors: Findings from the Dominican Republic

Abstract: Quantitative analyses exploring the relationship between masculinities and men's sexual risk behaviors have most commonly used one dimension of masculinities: men's gender ideology. Examining other dimensions may enhance our understanding of and ability to intervene upon this relationship. In this article, we examined the association between gender role conflict/stress (GRC/S)-men's concern about demonstrating masculine characteristics-and three different sexual risk behaviors (having two or more sex partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For example, integrating certain validated psychometric scales into survey data collection instruments could help answer key questions on this topic: are men with a more equitable gender ideology— as measured by Gender Equitable Men Scale [47]—more likely to test for HIV? Are men with greater concern about demonstrating masculine characteristics—as measured by the Gender Role Conflict/Stress scale [48, 49]—less likely to test for HIV? Are these relationships moderated by men’s social or geographic context (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, integrating certain validated psychometric scales into survey data collection instruments could help answer key questions on this topic: are men with a more equitable gender ideology— as measured by Gender Equitable Men Scale [47]—more likely to test for HIV? Are men with greater concern about demonstrating masculine characteristics—as measured by the Gender Role Conflict/Stress scale [48, 49]—less likely to test for HIV? Are these relationships moderated by men’s social or geographic context (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Situating our research within a larger body of work on cultural norms and expectations about masculinity in MSW in the DR helps to explain some of our findings. 26,34…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently conducted a qualitative exploration of men's peer group relationships -focusing on male peer groups and homosocial spaces -and found that most men lacked trusted friendships and many avoided friendships due to perceptions that peers would pressure them to behave in ways they did not want to (Fleming et al 2014). We also found that men's sexual behaviors and willingness to get tested for HIV is, in part, shaped by concerns of projecting a masculine image of strength to their social network (Fleming et al 2015, Fleming, Barrington, Powell, et al 2016).…”
Section: Previous Work On Caribbean and Dominican Masculinitiesmentioning
confidence: 92%